Phenotype, penetrance, and treatment of 133 cytotoxic T-lymphocyte antigen 4–insufficient subjects - Schwab, Charlotte; Gabrysch, Annemarie; Olbrich, Peter; Patiño, Virginia; Warnatz, Klaus; Wolff, Daniel; Hoshino, Akihiro; Kobayashi, Masao; Imai, Kohsuke; Takagi, Masatoshi; Dybedal, Ingunn; Haddock, Jamanda A.; et al. (Journal of allergy and clinical immunology, 2018)
Cytotoxic T-lymphocyte antigen 4 (CTLA-4) is a negative immune regulator. Heterozygous CTLA4 germline mutations can cause a complex immune dysregulation syndrome in human subjects. We sought to characterize the penetrance, clinical features, and best treatment options in 133 CTLA4 mutation carriers. Genetics, clinical features, laboratory values, and outcomes of treatment options were assessed in a worldwide cohort of CTLA4 mutation carriers. We identified 133 subjects from 54 unrelated families carrying 45 different heterozygous CTLA4 mutations, including 28 previously undescribed mutations. Ninety mutation carriers were considered affected, suggesting a clinical penetrance of at least 67%; median age of onset was 11 years, and the mortality rate within affected mutation carriers was 16% (n = 15). Main clinical manifestations included hypogammaglobulinemia (84%), lymphoproliferation (73%), autoimmune cytopenia (62%), and respiratory (68%), gastrointestinal (59%), or neurological features (29%). Eight affected mutation carriers had lymphoma, and 3 had gastric cancer. An EBV association was found in 6 patients with malignancies. CTLA4 mutations were associated with lymphopenia and decreased T-, B-, and natural killer (NK) cell counts. Successful targeted therapies included application of CTLA-4 fusion proteins, mechanistic target of rapamycin inhibitors, and hematopoietic stem cell transplantation. EBV reactivation occurred in 2 affected mutation carriers after immunosuppression. Affected mutation carriers with CTLA-4 insufficiency can present in any medical specialty. Family members should be counseled because disease manifestation can occur as late as 50 years of age. EBV- and cytomegalovirus-associated complications must be closely monitored. Treatment interventions should be coordinated in clinical trials.